Impact of Television Programs and Asvertisements of School Going Adolescents: A Case Study of Bahawalpur City, Pakistan - A. Hassan; M. Daniyal (University of Sofia, 2013)
Teenage is the most vital and delicate stage of human life. During teenage youngsters try to follow new fashion, culture and style which is being presented in different programs and advertisements on television. They have strong urge and inclination to adopt something new and extra ordinary different from their surroundings. In Pakistan, there are about 43.40% are the adolescents of the age between 13-16 years as stated by Federal Bureau of Statistics. Adolescents are the age group that is the most effected by T.V pro-grams and advertisements. Target audience of most of the programs and ad-vertisements area adolescents e.g. cell phone advertisements. Most of the children in different countries spend almost 3-4 hours per day in watching T.V as per statement of UNESCO. The effects of the commercials and T.V pro-grams on children vary from person to person. This research tries to dig out the impact of different T.V programs and ads on the children between the age group of 13-16 of different schools of Bahawalpur City.